Effect of heat shock on ribosome synthesis in Drosophila melanogaster. - Bell, J (1988)
In Drosophila tissue culture cells, the synthesis of ribosomal proteins was inhibited by a 1-h 37 degrees C heat shock. Ribosomal protein synthesis was repressed to a greater extent than that of most other proteins synthesized by these cells at 25 degrees C. After a 1-h heat shock, when the cells were returned to 25 degrees C, the ribosomal proteins were much slower than most other 25 degrees C proteins to return to pre-heat shock levels of synthesis. Relative to one another, all the ribosomal proteins were inhibited and later recovered to normal levels of synthesis at the same rate and to the same extent. Unlike the ribosomal proteins, the precursor to the large rRNAs was continually synthesized during heat shock, although at a slightly reduced level, but was not processed. It was rapidly degraded, with a half-life of approximately 16 min. Pre-heat shock levels of synthesis, stability, and correct processing were restored only when ribosomal protein synthesis returned to at least 50% of that seen in non-heat-shocked cells.